Importance of preoperative hematological parameters in patients undergoing surgical resection for colorectal cancer - Cayci, Haci Murat; Erdogdu, Umut Eren (The European Research Journal, 2017)
Objectives. Colorectal cancer has a high prevalence worldwide, and new predictive and prognostic factors are needed for its early diagnosis, treatment, and follow-up. In this study, we have investigated the relationship between colorectal cancer and neutrophil to lymphocyte ratio (NLR), mean platelet volume (MPV), and platelet to lymphocyte ratio (PLR) values. Methods. Data from 71 patients admitted to our hospital between May 2013 and May 2015, who underwent surgical resection for colorectal cancer, and met the criteria of the study, was evaluated retrospectively. NLR, MPV and PLR data detected in the preoperative period was noted. Demographic data, the presence of comorbidity, colonic localization of the tumor, colonoscopic findings, and surgical resection type and method were compared with the data of morbidity and mortality, lymphovascular and perineural invasion, lymph node and distant metastasis and stage of the disease. Results. No statistical significance was detected between preoperative NLR, MPV, and PLR, demographical data, the presence of comorbidity, colonic localization of the tumor, colonoscopic findings, surgical resection type and method and morbidity, lymph node and distant metastasis, lymphovascular invasion, or stage of the disease. However, a statistically significant relationship was detected between mortality development and NLR and PLR values (p=0.030; p=0.043; respectively). There was also a statistically significant relationship between the presence of perineural invasion and PLR (p=0.031). Conclusion. Hematological parameters (NLR, MPV, and PLR) evaluated in preoperative period in patients who have been applied surgical resection for colorectal cancer may help clinical and pathological staging.